Reliability and concurrent validity of Iphone®level application for measuring lower limb active flexion and extension range of motions in physical education students - Izzet Kırkaya; Celil Kaçoğlu; Beyza Şenol (Physical Education of Students)
Background and Study Aim. The aim of this study was to analyse reliability and validity of accelerometer-based Iphone® Level application for measuring lower extremity active flexion and extension joint range of motion.